First description of the female of Letana mursinga Ingrisch & Shishodia, 2000 (Orthoptera: Tettigoniidae; Phaneropterinae; Letanini) from India - Kumar, Hirdesh; Chandra, Kailash (Zootaxa, 2020)
Female of Letana mursinga Ingrisch & Shishodia, 2000 is described first time from Arunachal Pradesh, India along with a checklist of Indian species of Letana Walker, 1869. A map is also prepared for its distribution.